A retrospective observational study of maternal weight gain during pregnancy and correlation with fetomaternal outcome in women admitted to labour room in a tertiary care center of South Gujarat - Hadiya, Nitinkumar; Prajapati, Nilam; Udhanawala, Parul; Patel, Urmish; Shaikh, Ameena (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Gestational weight gain (GWG) is an important determinant of maternal and neonatal health. Both excessive and inadequate GWG are associated with adverse outcomes. This study evaluated the correlation of GWG, based on Institute of Medicine (IOM) guidelines, with pregnancy outcomes across different body mass index (BMI) categories. Methods: A retrospective observational study was conducted in the Department of Obstetrics and Gynaecology at a tertiary care centre in South Gujarat over one year. A total of 300 pregnant women were analysed for age, parity, BMI, GWG, and fetomaternal outcomes. Results: Most participants were aged 19–35 years (95%), with primipara comprising 40.67%. Poor GWG was observed in 56% and normal GWG in 35.67%. Preterm labour was more frequent in underweight women (11.13%), while post-term delivery was higher in obese women (17.47%). Vaginal delivery predominated in poor GWG (72.62%), whereas lower segment caesarean section (LSCS) rates were greater in high BMI groups (36%). Low birth weight (<2.5 kg) was common with poor GWG (41.07%), while birth weight >2.5 kg was more frequent in normal (76.63%) and excessive GWG (88%). Anaemia was the leading comorbidity (132 cases), particularly in underweight women. GDM, hypertensive disorders, big bay, induction failure, operative delivery, and postpartum complications were associated with higher BMI and excessive GWG. Conclusions: GWG followed pre-pregnancy BMI trends. Excessive GWG was linked with metabolic and obstetric complications, while below-recommended GWG increased risks of low birth weight, preterm delivery, and anaemia.